2019
DOI: 10.1083/jcb.201810058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomics reveals mitotic function of the ATR activator ETAA1

Abstract: The ATR kinase controls cell cycle transitions and the DNA damage response. ATR activity is regulated through two ATR-activating proteins, ETAA1 and TOPBP1. To examine how each activator contributes to ATR signaling, we used quantitative mass spectrometry to identify changes in protein phosphorylation in ETAA1- or TOPBP1-deficient cells. We identified 724, 285, and 118 phosphosites to be regulated by TOPBP1, ETAA1, or both ATR activators, respectively. Gene ontology analysis of TOPBP1- and ETAA1-dependent phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 39 publications
5
58
0
Order By: Relevance
“…Recent work from the Cortez lab showed that, in HCT116 cells, deletion of the AAD of ETAA1 did not inhibit ATR activation. However, attempts to delete the AAD of TopBP1 resulted in cell death, indicating that, at least in HCT116 cells, TopBP1 is the major activator of ATR (14). Thus, it is unlikely that ETAA1 could compensate for decreased TopBP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from the Cortez lab showed that, in HCT116 cells, deletion of the AAD of ETAA1 did not inhibit ATR activation. However, attempts to delete the AAD of TopBP1 resulted in cell death, indicating that, at least in HCT116 cells, TopBP1 is the major activator of ATR (14). Thus, it is unlikely that ETAA1 could compensate for decreased TopBP1.…”
Section: Discussionmentioning
confidence: 99%
“…ETAA1 was only recently discovered and less is known about the mechanism by which it activates ATR. However, recent work suggests that ETAA1 plays only a minor role in ATR activation during the DDR (14,15). Instead, ETAA1 plays a primary function in proper chromosome alignment and checkpoint activation in metaphase as well as preventing untimely entry into G2.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm that the diminished abundance of DNA end resection factors was caused by loss of ATR signaling, we monitored the abundance of these proteins upon genetic ablation of the ATR activators TOPBP1 and ETAA1. We used an HCT116-derivative cell line where the ATR Activating Domain (AAD) in the ETAA1 gene has been removed by CRISPR-Cas9, and both alleles of TOPBP1 were tagged with an mAID epitope to conditionally induce TOPBP1 degradation upon auxin treatment 44,45 (Fig. 1f).…”
Section: Chemical and Genetic Ablation Of Atr Signaling Depletes The mentioning
confidence: 99%
“…ETAA1 and TopBP1 converge at the phosphorylation of the ATR target RPA and, depending on the cellular context, of the ATR effector Chk1 (Checkpoint Kinase 1; 5, 6, 7, 8). However, by controlling specific subsets of ATR targets, ETAA1 and TopBP1 regulate parallel, independent branches of ATR signaling (9). Another important distinction between TopBP1 and ETAA1 is the way in which both ATR activators are recruited to DNA.…”
mentioning
confidence: 99%
“…While TopBP1 senses junctions between ssDNA and double-stranded DNA (dsDNA), ETAA1 interacts directly with RPA-ssDNA (1). Hence, ETAA1 might be more important than TopBP1 in unstressed cells because, while there is always availability of ssDNA at replicating forks, ss/dsDNA junctions increase only after replication stress (9, 10). In that sense, recent work demonstrated that ETAA1, but not TopBP1, controls basal ATR activity to keep FOXM1 in a hypo-phosphorylated inactive state (10).…”
mentioning
confidence: 99%